Downregulation of m6A Methyltransferase in the Hippocampus of Tyrobp–/– Mice and Implications for Learning and Memory Deficits - Lv, Zhanyun; Xu, Tongxiao; Li, Ran; Zheng, Dejie; Li, Yanxin; Li, Wei; Yang, Yan; Hao, Yanlei (Frontiers in Neuroscience, 2022)
Loss-of-function mutations in the gene that encodes TYRO protein kinase-binding protein (TYROBP) cause Nasu-Hakola disease, a heritable disease resembling Alzheimer’s disease (AD). Methylation of N6 methyl-adenosine (m6A) in mRNA plays essential roles in learning and memory. Aberrant m6A methylation has been detected in AD patients and animal models. In the present study, Tyrobp–/– mice showed learning and memory deficits in the Morris water maze, which worsened with age. Tyrobp–/– mice also showed elevated levels of total tau, Ser202/Thr205-phosphorylated tau and amyloid β in the hippocampus and cerebrocortex, which worsened with aging. The m6A methyltransferase components METTL3, METTL14, and WTAP were downregulated in Tyrobp–/– mice, while expression of demethylases that remove the m6A modification (e.g., FTO and ALKBH5) were unaltered. Methylated RNA immunoprecipitation sequencing identified 498 m6A peaks that were upregulated in Tyrobp–/– mice, and 312 m6A peaks that were downregulated. Bioinformatic analysis suggested that most of these m6A peaks occur in sequences near stop codons and 3′-untranslated regions. These findings suggest an association between m6A RNA methylation and pathological TYROBP deficiency.